A XIX-XX. század fordulójának magyar polgári, valamint a mai Szerbia - különös tekintettel a Vajdaságra - közigazgatásának rövid bemutatása - Deák, István (Közép-Európai Közlemények, 2011)
After the Austro-Hungarian Compromise of 1867 the territorial and mostly feudalistic local governments were abolished in Hungary. The county system became the fundamental and general basis of the public administration, for the first time in the history of the country. Despite and in line with this phenomenon the regionalism has appeared in the public administration so the departmental governance at the territoral level was very varied. The country planning of the municipalities was achieved by the Act XXXIII of 1876 which was applied with some small corrections until 1920. The most important element of the political transformation occured in the Central and Eastern European countries at the end of the XXth century was the restitution of the local governments. That was the case in Serbia and in Vojvodina where besides the province districts were established too. A district is a territorial unit of the public administration. Serbia is divided into 29 districts of which 7 can be found in Vojvodina.The municipality is the smallest unit of the public administration which is a territoral unit with several settlements. It can be matched to the old district in Hungary.